Investigation of abdominal pain to detect pancreatic cancer. Issue 7652 (8th May 2008) - Guthrie, J Ashley; Sheridan, Maria B
Abstract : When a patient presents with abdominal pain, which investigations should clinicians use to establish whether the pain results from pancreatic cancer?